Smartstay: A fast and secure web-based hotel booking system using HTML and PHP - Jamil Alsayaydeh, Jamil Abedalrahim; Fedorchenko, Ievgen; Oliinyk, Andrii O.; Alomari, Mohammad Ahmed; Wong, Adam Yoon Khang; Herawan, Safarudin Gazali; Mamchenko, Serhij (Asian Research Publishing Network, 2025)
The development of the online hotel booking system centered around the utilization of HTML for crafting the frontend interface, encompassing the design and layout of web pages. HTML played a pivotal role in providing the necessary structure and elements to present hotel information, room options, and booking forms seamlessly to users. The frontend was meticulously designed to be responsive, ensuring accessibility across various devices for a smooth user experience. On the backend, PHP was employed to manage and process data, handling user input, room availability, and reservation details. Leveraging PHP’s server-side scripting capabilities, the system seamlessly interacted with databases, facilitating dynamic content generation. Notable features of the online hotel booking system include a robust search functionality enabling users to find available hotels based on specified criteria, like dates and room preferences. Detailed information about each hotel, encompassing amenities, pricing, and room descriptions, was easily accessible. From the testing being done on the system, we have proved that the system has the best response time out of all the other booking systems, which is 27ms compared to other booking websites like Trivago(239ms), Hotels.com(1.47s), Expedia(2.02s), Booking.com(2.06s), and Agoda(286ms). The system also gathered an outstanding 4.29-star average rating from the survey being handed out to users. Based on the review percentage, the system collected a staggering 43% votes for 5-star, 46% votes for 4-star, 11% votes for 3-star, and 0% for both 2-star and 1-star. The system also prioritized a secure and user-friendly booking process, allowing users to effortlessly select their desired room and complete reservations with confidence. The rooms are also managed by the admins. In this case, admins can add, edit, or delete rooms, respectively, according to the situation. The availability of rooms can be changed by the admin, too.